SPEAKING SKILL AND PICTURE SERIES ON EFL CLASSROOM - Neneng Islamiah; Nurhasanah Nurhasanah (Universitas Lambung Mangkurat, 2019)
This study was aimed to find out whether by using this techniques can motivate students in speaking. Result shows that the students’ ability in speaking English has a better ability after the students having the treatment. It is also proves that the application of procedures in using pictures series can also improve the students ability in speaking in five terms according to Oller,John W, they are accent, vocabulary, grammar, fluency, and comprehend. The purpose of the study aims to investigate whether the ability of the students after they have had treatment have better in the ability than before. This study was administered to the eleventh grade students of MIPA on SMAN7 Banjarmasin. The results of the research show that the teaching techniques can improve students speaking ability in both the first cycle and the second cycle, but the researcher only took 18 students for this study because their ability in speaking English is medium to low in ability in contrast to other students. This finding also proves that students’ ability. It also proves that the application of procedures in using serial pictures can improve the ability of English speaking students in five terms as mention before. From the data analysis the value of significant column p- 2tailed at the table show .000 which is lower than 0.05. That is the researcher conclude that; accent, vocabulary, grammar, fluency and also comprehension, the formulated null hypothesis was rejected. Regarding the result of the research showed that it did work.